2006
DOI: 10.1128/aem.72.1.565-574.2006
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Mycobacterium avium subsp. paratuberculosis and Other Zoonotic Pathogens during Simulated Composting, Manure Packing, and Liquid Storage of Dairy Manure

Abstract: Livestock manures contain numerous microorganisms which can infect humans and/or animals, such asEscherichia coli O157:H7, Listeria monocytogenes, Salmonella spp., and Mycobacterium avium subsp. paratuberculosis (Mycobacterium paratuberculosis). The effects of commonly used manure treatments on the persistence of these pathogens have rarely been compared. The objective of this study was to compare the persistence of artificially inoculated M. paratuberculosis, as well as other naturally occurring pathogens, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 32 publications
4
95
0
2
Order By: Relevance
“…The effect of those changes on the survival of MAP on pastures or fields is also unclear. Furthermore, while the detection of viable MAP is greatly reduced in thermophilic compost compared to liquid manure, MAP DNA can be detected in compost up to 56 days and liquid manure up to 175 days [75]. Composting has also been shown to be ineffective for decontamination of carcasses infected with MAP, even after 250 days [76].…”
Section: Crop Managementmentioning
confidence: 97%
“…The effect of those changes on the survival of MAP on pastures or fields is also unclear. Furthermore, while the detection of viable MAP is greatly reduced in thermophilic compost compared to liquid manure, MAP DNA can be detected in compost up to 56 days and liquid manure up to 175 days [75]. Composting has also been shown to be ineffective for decontamination of carcasses infected with MAP, even after 250 days [76].…”
Section: Crop Managementmentioning
confidence: 97%
“…Compost has been shown to be effective to kill pathogens and indicator bacteria present in livestock manure (Grewal et al, 2007;Grewal et al, 2006;Jiang et al, 2003;Lemunier et al, 2005;Tiquia, 2005). In surveying abundance of a large number of tet genes and erm genes, composted manure was found to contain much less AMR genes, up to seven orders of magnitude, than fresh manure or manure treated by other technologies, including lagoon, aerobic treatment, and anaerobic treatments (Chen et al, 2010;Chen et al, 2007;Yu et al, 2005).…”
Section: Compostingmentioning
confidence: 99%
“…Another study showed that this bacterium can survive for 48 weeks in shaded water sediment and 12 weeks in the ground (Whittington et al, 2005), and if MAP was mixed with manure and stored in a shaded place it could even be detected by culture after a period of 55 weeks (Whittington et al, 2004). High temperature, ultraviolet radiation, as well as low pH and humidity are known to reduce the survival time of MAP in the environment (Sung and Collins, 2003;Whittington, et al, 2004;Grewal et al, 2006).…”
Section: Grass Silage Contaminated With Mycobacterium Avium Subspeciementioning
confidence: 99%
“…The viability of MAP in the environment depends on temperature, humidity, pH (Grewal et al, 2006) and ultraviolet radiation (Whittington et al, 2004). While temperature and UV light can be considered to be of negligible or no influence at all for the survival of MAP in silage bales, humidity and pH as well as the concentration of ammonia could be responsible for the short life span of the bacteria within the milieu of the bales.…”
Section: Detection Of Map Culture and Real-time Qpcrmentioning
confidence: 99%